Short Communication: Correlation of flowering phenology and heat unit of forest cloves (Syzygium obtusifolium) at different elevations in Maluku Province, Indonesia - MARWAN YANI KAMSURYA; AMBO ALA; YUNUS MUSA; RAFIUDDIN RAFIUDDIN (Society for Indonesian Biodiversity, 2022)
Abstract. Kamsurya MY, Ala A, Musa Y, Rafiuddin. 2022. Short Communication: Correlation of flowering phenology and heat unit of forest cloves (Syzygium obtusifolium) at different elevations in Maluku Province, Indonesia. Biodiversitas 23: 5593-5599. The phenology and heat unit of the forest clove (Syzygium obtusifolium L.) are important parameters for the efficient maintenance of this plant. This study aimed to describe phenological flowering stages (PFS) and calculate growing degree days for different PFS, which will have a big impact on crop management and understanding the impact of climate variables on crucial phenological events. The research was conducted in Ambon, Maluku Province, Indonesia, for 16 months, from January 2020 to May 2021. Five sample points at different elevations were determined purposively, i.e: Halasi (6 m above sea level (m asl)), Tibang (11 m asl), Oli (125 m asl), Wanat (175 m asl), and Telaga Kodok (214 m asl). The phenology of flowering is separated into 6 stages: the flowering primordia, the appearance of the flower stalk, the perfect flower stalk, the appearance of the flower bud, the flower is fully formed, and the flower starts to bloom. The results showed that the phenological cycle of the forest clove plant was flowering periodically for 365 days. The average temperature of PFS (29oC) in Halasi was higher compared to other locations. It indicates that the lower the altitude, the faster the flowering period. This study found significant correlations between altitude and PFS, except flower stalks appear and flowers will appear. The phenology of clove plants is influenced by the accumulation of heat units, with the highest heat unit value in the flowers start to bloom stage, ranging from 2,983.23 dayso (Telaga Kodok) to 3,128.84 dayso (Halasi). As elevation increases, the number of heat units decreases, so the PFS is delayed. The primordial phase in Halasi appears in August-September while at Telaga Kodok in December.